INNOVATIVE METHODS FOR DEVELOPING INDEPENDENT THINKING SKILLS IN PRIMARY SCHOOL STUDENTS - Shavazova Nilufar Musayevna (Western European Studies, 2025)
This article discusses the relevance of developing independent thinking skills in primary school students, the innovative methods used in this process, and the importance of modern pedagogical technologies in the educational process of independent thinking and the development of students as complete individuals.
Keywords: independent thinking; primary education; innovative methods